Desain Bangunan dan Fasilitas Restoran Ramah Keluarga dan Relevan dengan Budaya Urban Kota Denpasar - Ni Made Emmi Nutrisia Dewi; Ni Nyoman Sri Rahayu; I Kadek Pranajaya; Kadek Abe Jantika (ATRIUM: Jurnal Arsitektur, 2023)
Title: The Design of Buildings and Restaurant Facilities that are Family Friendly and Relevant to the Urban Culture of Denpasar   The urban community's demand to bring families to visit restaurants is significantly high. The on-site phenomenon indicates that the building designs of several restaurants in Denpasar have not maximally met the needs of the urban community, especially for families. Therefore, research is required to analyze restaurants' facilities and building designs to align with the needs of families and urban culture in Denpasar. The method employed is a qualitative descriptive method. The research results showcase the case study objects of several favorite restaurants in Denpasar, indicating that some already meet the needs of the urban community but need to be adjusted to align with current needs. The findings show that some restaurants are not in line with urban culture due to insufficient attention to the needs of the urban community. Issues related to spatial completeness and arrangement, availability of specific facilities, furniture design, and cleanliness of facilities contribute to this mismatch. The solution is to consider standard design, space, and security to meet needs, provide specific facilities, and implement the concept of green design. The contribution provided is in the form of input to ensure that restaurants are designed to adapt to the evolving needs of the urban community.